SUCCESSFUL PREGNANCY OUTCOME IN PATIENT WITH CONGENITAL ADRENAL HYPERPLASIA - Bitoska, Iskra; Mishevska, Saha Jovanovska; Todorova, Biljana Jovanovska; Zivkovik, Marija; Stojkoska, Ivana Mladenovska; Zafirova, Biljana (Journal of Morphological Sciences; Vol 1 No 2 (2018): JMS, 2018)
Introduction : The term congenital adrenal hyperplasia (CAH) encompasses a group of autosomal recessive disorders, which involves a deficiency of an enzyme involved in the synthesis of cortisol, aldosterone, or both. There are two forms of CAH: classic, devided into salt-waisting and simple virilizing, and non-clasic form. Fertility is relative in CAH, but the incidence of spontaneous miscarriage is higher Case report : We present Ð° patient with simple virilising form of CAH and pregnancy. Our patient was admitted in the hospital in 2014 when we diagnosed simple virilisng form of CAH. She came with history of two unsuccesfull IVFâ€™s, in 2013 and 2014. Dexamethason  therapy was introduced. In preparation for conception, the steroid replacement was changed to Prednisolon. There was one more IVF performed, in 2016, again without succes. Our patient concieved naturally  in august 2017. The screening conducted at the first visit of 14 weeks of gestation was normal and further tests conducted at gynaecologist were also normal. During pregnancy, she continued to take prednisolone (minimum dose 7.5 mg/day to maximum dose 20 mg/day). Check ups were done each two months.  She delivered female, weighs 2.9 kg by elective cesarean section at 38+1 week of gestation. The baby exhibited normal Apgar score. The external genitalia were normal. After the delivery, the patient had taken prednisolone (15 mg/day) consistently for the CAH. Conclusion : Choosing the appropriate type and dose of steroid replacement is quite challenging in the treatment of women with classical CAH desiring pregnancy.Succesfull management of CAH in pregnancy requires a firm knowledge of endocrine changes that occur  during gestation. From a fetal and neonatal standpoint, accurate prenatal diagnosis alows good prenatal treatment in an attept to minimize clinical problems in the neonates.